PELATIHAN KADER DALAM PENYULUHAN DI POSYANDU DESA JAYASAKTI KECAMATAN MUARAGEMBONG KABUPATEN BEKASI - Tati Nuryati; Handayani, Handayani; Nadela Selfa; Khoirunnisa Dwi Lestari; Diana Widyaningsih; Annisa Aireka; Zulhasanah Insani Pattimura; Adinda Nabila Puteri Munir; Nilam Ayu Kurniasari (Bajang Institute, 2025)
Increasing the skills of health cadres must be carried out periodically to improve the quality of health services (Rufiati et al., 2011). One of the skills of health cadres in implementing the infant and toddler program is that cadres measure the upper arm circumference (LILA) and body weight of infants and toddlers. Cadres also record measurement results and explain conclusions for follow-up by authorized health personnel. Based on the results of the preliminary study, the government has carried out socialization on training for 25 cadre skills and has been carried out by the community health center and the PKK of Pokja 4 District to increase cadre capacity, but it was found that the cadres' abilities in the field of infant and toddler skills are still relatively low. This extension training for diposyandu cadres aims to improve the ability of posyandu cadres in carrying out counseling. This program involves postgraduate students from the Public Health Science Management Study Program (MIKM) as facilitators, in collaboration with the Community Health Center. Activities carried out in the initial stages include coordinating with the Muaragembong Community Health Center, cadre training activities are carried out with several activities, namely conducting pre-tests, providing material related to assessing the results of anthropometric measurements on babies and toddlers and effective communication material, role play activities, Foccus Group Discussion (FGD) then post test. The evaluation results showed a significant increase in knowledge, with the difference between the pre-test and post-test scores reaching 66% from a poor pre-test frequency of 24 to a poor post-test frequency of 8. The evaluation results show significant increase in knowledge, with a difference between pre-test scores and post-test. Even though there were obstacles such as limited access to health and bad weather, the support of the community health center and the participation of cadres made this program a success